Economic Valuation of Monument Park 45 Banjarsari Solo City - Lia Kusumaningrum; Muh Faqih Muhaimin Fathoni; Naila Maulida Ibriza; Tsalatsun Ikhwa Muazulfa; Yaqut Amjad AdillahRaharjo; Lintang Suminar (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2024)
Monument Park 45 Banjarsari is one of the icons of Solo City which is in Banjarsari District. This city park was built on a land area with an area of 17,688 m². Making city parks and green belts is an action taken by the city government of Solo to preserve green open spaces in the city of Solo. This study aims to (1) calculate the economic value of a city park including indirect use value, choice value, inheritance value, and existence value (2) find out the public's perception of the physical and non-physical conditions of Taman Kota Monument 45 Banjarsari. This research was conducted by collecting questionnaire/interview data and calculating the number and circumference of trees. The sample used in this research was 50 visitors to Monument Park 45 Banjarsari, and the WTP and TCM methods were used to obtain recreation, existence and heritage values. The economic valuation generated through calculations using the WTP and TCM methods shows that the economic value of carbon is IDR 3.137.471.289; Recreation economic value of IDR 530,388,800; Inheritance economic value of IDR IDR 386,140,800; and The economic value of existence is IDR 100,418,800.